Comparison between use of combination of mifepristone and misoprostol versus misoprostol alone in the management of intrauterine fetal death - Talasani, Sreeveena; Venkamolla, Pran Hitha; Betha, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Intrauterine fetal death (IUFD) is estimated to occur in 1% of all pregnancies. The advent of prostaglandins has revolutionized the management of IUFD. There are limited studies using a combined regimen of mifepristone and misoprost for induction of labor in IUFD. Hence this study was undertaken to assess the efficacy and safety of combined regimen with misoprostol alone, in the management of IUFD. Methods: This hospital based prospective study included 60 pregnant women with IUFD admitted at Mediciti Institute of Medical Sciences, during the period January 2015 to July 2016. An ultrasound scan was performed to confirm IUFD and localize the placenta. Women were divided alternatively into 2 groups with 30 in each group (group 1- women received 200 mg mifepristone orally followed by misoprostol after 24 hours & in group 2, 100 µg misoprostol every 6 hourly for a maximum of 4 doses between gestational age 24-26 weeks, 25-50 µg 4 hourly for a maximum of 6 doses beyond 26 weeks). Results: The mean induction to delivery interval was 10 hours in group 1 and 16.3 hours in group 2 (p value 0.007). Mean dose of misoprostol required in group 1 was 1.87 and 2.67 in group 2 (p value 0.008). With respect to side effects, the two groups did not differ significantly. Conclusions: The combined regimen was more effective than misoprostol for the induction of labour in IUFD, in terms of higher rate of successful delivery and shorter induction to delivery interval.